2006
DOI: 10.1177/000313480607201205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bacterial Contamination on Neointimal Hyperplasia in Vascular Grafts

Abstract: Neointimal hyperplasia (NH) is the most significant contributing factor to long-term vascular graft failure. Inflammation is known to be important in its development; however, the role of bacterial infection is unclear. We examined the effect of contamination with common organisms on the development of NH in expanded polytetrafluoroethylene grafts. Thirty adult pigs were randomized into one of four groups: no infection, contamination with Staphylococcus aureus, mucin-producing Staphylococcus epidermidis, or Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In animal models Pseudomonas has been found to affect vascular grafts. Disruption of venous grafts was demonstrated in a canine model , and increased neointimal hyperplasia, known to be a contributing factor for vascular graft failure, was found in vascular grafts of pigs infected with Pseudomonas .…”
Section: Discussionmentioning
confidence: 97%
“…In animal models Pseudomonas has been found to affect vascular grafts. Disruption of venous grafts was demonstrated in a canine model , and increased neointimal hyperplasia, known to be a contributing factor for vascular graft failure, was found in vascular grafts of pigs infected with Pseudomonas .…”
Section: Discussionmentioning
confidence: 97%
“…A recent study 20 suggested that subclinical infection might be a significant factor contributing to neointimal hyperplasia. Therefore, we tested the hypothesis that Pg may participate in or promote intimal hyperplasia after the occurrence of significant vascular perturbations in a rabbit model of single balloon injury to the iliac artery.…”
mentioning
confidence: 99%